CORRELATION STUDY OF INTEREST IN LISTENING TO ENGLISH SONGS AND LISTENING ACHIEVEMENT - Noventa Harlyn, Helen; ., Sudarsono; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: This research was to investigate the correlation of interest in listening to English songs and listening achievement to Semester - 3 Students of English Language Education Study Program, Teacher Training and Education Faculty, Tanjungpura University, in Academic Year 2015/2016. It was a correlation study. The research participants were 54 students. The data were collected by administering closed-ended questionnaires and multiple choice questions of listening comprehension test. Then, the data were calculated by using Pearson Product Moment Correlation Coefficient formula. Based on the research finding, the r (correlation coefficient) value of the two variables was 0.769. The obtained t-value was higher than the value of t-table at 1% (0.01) level of significance with degree of freedom (df) = 52 (8.658 > 2.673). It finds out there is a significant correlation of interest in listening to English songs and listening achievement. Keywords: correlation, interest, English Songs, listening achievement Abstrak: Penelitian ini bertujuan untuk mengetahui sejauh mana korelasi ketertarikan mendengarkan lagu-lagu berbahasa Inggris terhadap kemampuan mendengar mahasiswa semester 3 Program Studi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Tanjungpura, Tahun Ajaran 2015/2016. Penelitiaan ini merupakan penelitiaan korelasi. Jumlah sampel pada penelitian ini adalah 54 mahasiswa. Data di kumpulkan menggunakan kuestioner bentuk tertutup dan soal komprehensif mendengarkan berbentuk pilihan ganda. Kemudian, data dihitung menggunakan rumus Pearson Product Moment Correlation Coefficient. Berdasarkan hasil penelitian, nilai r (koefisien korelasi) pada kedua variabel adalah 0.769. Nilai t yang diperoleh lebih tinggi dibandingkan dengan nilai t yang terdapat dalam t-table pada tingkat signifikan 1% (0.01) dengan derajat kebebasan = 52 (8.658 > 2.673). Hal ini mengindikasikan ada korelasi yang signifikan antara ketertarikan mendengarkan lagu-lagu berbahasa Inggris terhadap kemampuan mendengar mahasiswa. Kata kunci: korelasi, ketertarikan, lagu ? lagu berbahasa Inggris, kemampuan mendengarkan